The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1158/0008-5472.can-07-2674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Ras-Net (Elk-3) Pathway by a Novel Pyrazole that Affects Microtubules

Abstract: Net (Elk-3/SAP-2/Erp) is a transcription factor that is phosphorylated and activated by the Ras-extracellular signal-regulated kinase (Erk) signaling pathway and is involved in wound healing, angiogenesis, and tumor growth. In a cellbased screen for small molecule inhibitors of Ras activation of Net transcriptional activity, we identified a novel pyrazole, XRP44X. XRP44X inhibits fibroblast growth factor 2 (FGF-2)-induced Net phosphorylation by the Ras-Erk signaling upstream from Ras. It also binds to the colc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 47 publications
5
55
0
Order By: Relevance
“…We confirmed that these bands are down-regulated by siRNAs against Net in 444 (data not shown), similar to other cell lines we have studied (8,21). As reported previously, there is an additional non-identified band (n.i.)…”
Section: Hypoxia Has Different Effects On Net and Hif1␣ Proteinsupporting
confidence: 92%
See 1 more Smart Citation
“…We confirmed that these bands are down-regulated by siRNAs against Net in 444 (data not shown), similar to other cell lines we have studied (8,21). As reported previously, there is an additional non-identified band (n.i.)…”
Section: Hypoxia Has Different Effects On Net and Hif1␣ Proteinsupporting
confidence: 92%
“…Levels-To study the integration of Net in the hypoxia/PHD/ HIF1␣ signaling pathway, we compared the hypoxic regulation (8,21). We confirmed that these bands are down-regulated by siRNAs against Net in 444 (data not shown), similar to other cell lines we have studied (8,21).…”
Section: Hypoxia Has Different Effects On Net and Hif1␣ Proteinsupporting
confidence: 58%
“…Previous studies demonstrated that ELK3 participates in the regulation of various genes, including c-fos, egr-1, and PAI-1. In addition, ELK3 is known as a regulator of HIF-1α expression by modulating HIF-1α stability (21)(22)(23)30,31). HIF-1α plays a key role in the induction of cancer invasion, metastasis and angiogenesis, as well as in cancer growth, glucose metabolism, and other metastasis-associated signaling pathways (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…ELK3 is activated by mitogen-activated protein kinase (MAPK)-associated pathways, such as the Ras/extracellular signal-regulated kinase (ERK) and p38 pathways, and it plays an important role in various physiological processes, including cell migration, invasion, wound healing, angiogenesis and tumorigenesis, via the regulation of c-fos, early growth response protein 1 (egr-1), and plasminogen activator inhibitor-1 (PAI-1) (19)(20)(21)(22)(23). Mutations in ELK3 disrupt vasculogenesis, angiogenesis and wound healing in mice during development and in adulthood (24,25).…”
Section: Elk3 Promotes the Migration And Invasion Of Liver Cancer Stementioning
confidence: 99%
See 1 more Smart Citation